Ambient noise analysis for characterizing sub-surface dynamic parameters - B., Setiawan; T., Saidi; A., Yuliannur; U., Polom; Putra Jaya, Ramadhansyah; Mohamad Idris, Ali (2019)
Ambient noise analysis of horizontal to vertical spectral ratio (HVSR) method has been used widely to provide reliable estimates of the site fundamental frequency and to constrain the inversion of near-surface shear wave velocity. The present paper focuses on the site measurement using the aforementioned analysis by means of the HVSR method for characterizing sub-surface dynamic parameters in the City of Banda Aceh, Indonesia. A Guralp CMG-6TD broadband seismometer was used in this study to cover a wide frequency range from 0.033 Hz to 50 Hz in standard operation. The instrument was deployed at two different sites (i.e. Location#1 of Blang Padang and Location#2 of Stadion Dirmutala) in the City of Banda Aceh for at least 2 hours for ambient noise recording. This continuous of 2 hours’ microtremor time series was separated into 30 minutes record from which the site fundamental frequency and shear wave velocity of the measured site were deduced. The later sub-surface dynamic parameter was validated using another technique of reflection seismic. This investigation suggests the fundamental frequency of 0.45 Hz at Location#1 and of 0.65 Hz at Location#2. The estimated shear wave velocity of the top 30 m, Vs,30 of this investigation is 165 m/s at Location#1 and 156 m/s at Location#2. Both the site fundamental frequency and shear wave velocity are important for infrastructure design in the high seismic region of Banda Aceh, Indonesia.